Kelas Ibu Hamil Dalam Upaya Mengatasi Kecemasan Kehamilan - Maudy Lila Kartika (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
Anxiety in pregnancy were an important problem. The pregnancy anxiety rate in developing countries was around 1-37%, while in Indonesia it was around 10-25%. Anxiety had a bad impact on pregnancy, and it needs to be fixed. Maternity class is a program to enrich the knowledge of mothers and expected to minimize the mother’s anxiety. Based on the prior study, it was found that the maternity class program had not been effectively implemented. The purpose was to determine the effect of maternity class intervention to the anxiety of primigravida. This was a quasi-experimental with a one group pre-test post-test design. The sampling technique was purposive sampling with 20 respondents. This used Hamilton Anxiety Rating Scale (HARS) questionnaire. Statistical analysis used paired T test. The results showed a P value of 0.000, it means that maternity class could influence the level of pregnant women anxiety. As a conclusion, there was a significant effect after being given maternity class on the anxiety level of pregnant women, therefore the maternity class program should be carried out optimally.